2008
DOI: 10.1002/meet.2008.1450450256
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted image similarity criteria as revealed by sorting tasks

Abstract: This paper reports a study on the types of image categories constructed from magazine photographs. A novel sorting procedure was tested with the aim of providing more data on image similarity and possible category overlap. Expert and non-expert participants were compared in their categorizations. The new similarity sorting procedure resulted in an average of 67%-111% increase in similarity data gathered compared to basic free sorting. Categories were constructed on various levels of similarity: image Function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Various image sorting procedures and subsequent category naming have been utilized in studies of image similarity see e.g. 41 and may be applied to image quality evaluations as well. Engeldrum 37 discusses different approaches to defining the quality attributes used in scaling: defining the attribute in the textual/verbal instructions, use of visual references as anchors and letting the viewer define the attribute using some internal criteria.…”
Section: Methodological Approaches To Subjective Quality Evaluationmentioning
confidence: 99%
“…Various image sorting procedures and subsequent category naming have been utilized in studies of image similarity see e.g. 41 and may be applied to image quality evaluations as well. Engeldrum 37 discusses different approaches to defining the quality attributes used in scaling: defining the attribute in the textual/verbal instructions, use of visual references as anchors and letting the viewer define the attribute using some internal criteria.…”
Section: Methodological Approaches To Subjective Quality Evaluationmentioning
confidence: 99%
“…Most previous studies have involved a descriptive analysis of the category labels used but have not generated a hierarchical image categorization framework. Laine‐Hernandez and Westman (2008), however, employed a qualitative data‐based analysis on the category names given by their participants and produced the framework for magazine image categorization shown in Table 1.…”
Section: Introductionmentioning
confidence: 91%
“…between people, animals and inanimate objects as well as according to whether the scenes and objects in the images are man‐made or natural, e.g. buildings vs. landscapes (Laine‐Hernandez & Westman, 2008; Mojsilovic & Rogowitz, 2001; Teeselink et al, 2000). Laine‐Hernandez and Westman (2006) found that people also create image categories based on abstract concepts related to emotions or atmosphere, cultural references and visual elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content-based techniques for key-frame extraction have not yet been developed to the point where they are robust or effective in dealing with large collections (Smeaton, Wilkins, Worring, de Rooij, Chua, & Luan, 2008). displacement/atmosphere, emotional cue) Rorissa & Iyer (2008) basic (e.g., chair) subordinate superordinate (e.g., furniture) -(e.g., rocking chair) Laine-Hermandez & visual (color, composition, people (person, social affective (emotion, mood), photography Westman (2008) shape), meta-description status, etc. ), object (buildings, theme, function (illustration, (distance, B & W, (property, number) animals, etc.…”
Section: Introductionmentioning
confidence: 99%